2000
DOI: 10.1055/s-2000-10007
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Varicella Syndrome:a Rare Case of Central Nervous System Involvement Without Dermatological Features

Abstract: An unusual case of congenital varicella syndrome with significant central nervous system involvement, but without dermatological features at birth is described. The mother contracted chicken pox at 15 weeks' gestation. Congenital varicella syndrome involves multiple systems, but rarely without skin lesions identifiable at birth. Although varicella infection in pregnant women is an uncommon complication, the fetal embryopathy that may result can be devastating. Antenatal diagnosis of fetal embryopathy during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…13 In other words, although this infection is uncommon in pregnant women, the resulting foetal embryopathy can be devastating. 14,15 In this study, we found that 72.7% of young women who intend to marry were immune to chickenpox. In a similar study conducted in Turkey, 77.8% of 4387 subjects under age 30 were seropositive for VZV.…”
Section: Discussionmentioning
confidence: 69%
“…13 In other words, although this infection is uncommon in pregnant women, the resulting foetal embryopathy can be devastating. 14,15 In this study, we found that 72.7% of young women who intend to marry were immune to chickenpox. In a similar study conducted in Turkey, 77.8% of 4387 subjects under age 30 were seropositive for VZV.…”
Section: Discussionmentioning
confidence: 69%